2016
DOI: 10.1021/acs.jproteome.6b00452
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcriptomic and Proteomic Analysis of the Posterior Salivary Gland from the Southern Blue-Ringed Octopus and the Southern Sand Octopus

Abstract: This study provides comprehensive proteomic profiles from the venom producing posterior salivary glands of octopus (superorder Octopodiformes) species. A combined transcriptomic and proteomic approach was used to identify 1703 proteins from the posterior salivary gland of the southern blue-ringed octopus, Hapalochlaena maculosa and 1300 proteins from the posterior salivary gland of the southern sand octopus, Octopus kaurna. The two proteomes were broadly similar; clustering of proteins into orthogroups reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 75 publications
(200 reference statements)
8
41
0
Order By: Relevance
“…Octopus venom proteases specifically target muscle attachment sites in crabs, which allows the octopus to easily extract their muscle tissue [ 43 , 44 , 45 ]. In accordance with this venom role serine protease transcripts are the most highly expressed venom protein transcripts in both octopus and cuttlefish posterior salivary glands [ 35 , 36 , 46 , 47 ]. A similarly high level of PS1 expression in remipede venom glands is compatible with the idea that they too use their venom to detach the soft tissue of their prey from the exoskeleton, helping with prey ingestion and pre-digestion.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Octopus venom proteases specifically target muscle attachment sites in crabs, which allows the octopus to easily extract their muscle tissue [ 43 , 44 , 45 ]. In accordance with this venom role serine protease transcripts are the most highly expressed venom protein transcripts in both octopus and cuttlefish posterior salivary glands [ 35 , 36 , 46 , 47 ]. A similarly high level of PS1 expression in remipede venom glands is compatible with the idea that they too use their venom to detach the soft tissue of their prey from the exoskeleton, helping with prey ingestion and pre-digestion.…”
Section: Resultsmentioning
confidence: 96%
“…Likewise, PS1 enzymes are represented by the highest transcript diversity of all venom proteins, a result that corresponds closely to our initial study [ 12 ]. Serine peptidases are present in a broad range of venoms, but the extraordinarily high level of expression in remipede venom glands most closely parallels the expression found in the venom glands of some predators such as vipers, helodermatid lizards, and cephalopods [ 35 , 36 , 37 , 38 , 39 ]. PS1s could play a variety of roles in remipede venom.…”
Section: Resultsmentioning
confidence: 99%
“…The cephalopod venom apparatus comprises two pairs of histologically different venom glands, named posterior and anterior venom glands [58]. Whereas analyses on the posterior venom glands in cephalopods revealed toxins that convergently evolved in other venomous animals [5961], the role of the anterior glands remains poorly investigated. These glands are considered as mucus secreting organs [58] but their contribution to the cephalopod venom cocktail remains unclear, even though it was recently shown that they may also express some toxin transcripts [62].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are few transcriptomes of cephalopod venom glands that can provide information on expression within the tissue . Despite this, a dynamic evolutionary picture is emerging, for example, a loss of tachykinin expression in the venom gland has been observed in the southern blue‐ringed octopus ( Hapalochlaena maculosa ) . Due to the inclusion of the potent non‐proteinaceous neurotoxin tetrodotoxin (TTX) in H. maculosa , proteinaceous neurotoxins are considered to be redundant.…”
Section: Gene Duplications Explain Lineage‐specific Adaptations In Cementioning
confidence: 99%